The Elusive Evidence of Volcanic Lightning - Genareau, K. (Sci Rep, 2017)
Lightning strikes are known to morphologically alter and chemically reduce geologic formations and deposits, forming fulgurites. A similar process occurs as the result of volcanic lightning discharge, when airborne volcanic ash is transformed into lightning-induced volcanic spherules (LIVS). Here, we adapt the calculations used in previous studies of lightning-induced damage to infrastructure materials to determine the effects on pseudo-ash samples of simplified composition. Using laboratory high-current impulse experiments, this research shows that within the lightning discharge channel there is an ideal melting zone that represents roughly 10% or less of the total channel radius at which temperatures are sufficient to melt the ash, regardless of peak current. The melted ash is simultaneously expelled from the channel by the heated, expanding air, permitting particles to cool during atmospheric transport before coming to rest in ash fall deposits. The limited size of this ideal melting zone explains the low number of LIVS typically observed in volcanic ash despite the frequent occurrence of lightning during explosive eruptions.